A sol resin slurry and a method for preparing the same

CN121948926BActive Publication Date: 2026-10-23SHANDONG LUCHEN DIKE NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610148998.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-03
Publication Date
2026-10-23
Estimated Expiration
2046-02-03

AI Technical Summary

Technical Problem

但其粘度通常较高,且固化需要强酸性催化剂,限制了其在低粘度注浆领域的应用

Benefits of technology

[0057]1、优异的渗透性:A组分中改性硅溶胶的纳米粒子特性及低粘度呋喃树脂的引入,配合渗透助剂,使混合浆液初始粘度低(<10mPa·s),可渗入宽度小于0.1mm的微细裂隙。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a sol resin slurry and a preparation method thereof, and relates to the technical field of geotechnical engineering and building materials. The sol resin slurry comprises A component and B component; the A component is prepared from raw materials comprising the following components in parts by weight: modified silica sol 70-90 parts, furan resin prepolymer 10-30 parts, and penetration aid 0.1-1 part; and the B component is an acidic catalyst solution prepared from raw materials comprising the following components in parts by weight: organic acid 10-20 parts, slow-release agent 1-5 parts, and water 75-89 parts. The slurry is prepared by compounding the specially modified silica sol and the furan resin precursor, and the synergistic gelation and solidification are realized under mild acidic conditions; the obtained consolidated body has rigidity and durability of inorganic materials and toughness and high bonding strength of organic materials, and is suitable for precise anti-seepage and reinforcement of geotechnical and concrete structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of geotechnical engineering and building materials technology, and in particular to a sol-resin slurry and its preparation method. Background Technology

[0002] In fields such as water conservancy projects, tunnel support, foundation reinforcement, and historical building restoration, seepage prevention and reinforcement of soil and concrete structures is a key technical aspect. Currently, commonly used chemical grouts mainly include acrylate grouts, polyurethane grouts, epoxy resin grouts, and traditional water glass grouts. Acrylate grouts are environmentally friendly but have relatively low strength; polyurethane grouts have good elasticity but insufficient aging resistance and are relatively expensive; epoxy resin grouts have high strength but high viscosity, making them difficult to inject into micro-cracks; traditional water glass (sodium silicate) grouts are widely available and inexpensive, but suffer from problems such as difficulty in precisely controlling gel time, low strength of the solidified body, susceptibility to alkali-aggregate reaction, and poor long-term stability.

[0003] Silica sol is a dispersion of nano-SiO2 particles in water. Its colloidal particles are small in size and have good permeability. After gelation, it exhibits excellent weather resistance and environmental friendliness. However, pure silica sol solids are brittle, and their bonding strength with the substrate needs to be improved. The range of gelation time control based solely on dehydration or pH changes is limited.

[0004] Furan resins are known for their excellent resistance to acid and alkali corrosion, high mechanical strength, and good compatibility with inorganic materials, and are often used in corrosion-resistant flooring or linings. However, their viscosity is usually high, and curing requires a strong acid catalyst, which limits their application in low-viscosity grouting.

[0005] In existing technologies, there are few reports of combining nano-silica sol with furan resin and achieving synergistic gelation and curing under mild conditions through specific modification of the silica sol. Therefore, it is of great significance to develop a novel chemical slurry that combines excellent permeability, controllable gelation time, high consolidation strength, strong adhesion, and good durability. Summary of the Invention

[0006] The purpose of this invention is to provide a sol-resin slurry and a method for preparing the same, so as to at least partially solve the above-mentioned problems of the prior art.

[0007] To achieve the above objectives, the present invention provides a sol-resin slurry comprising component A and component B;

[0008] Component A is made from the following raw materials in parts by weight:

[0009] Modified silica sol: 70-90 parts

[0010] Furan resin prepolymer: 10-30 parts

[0011] Penetration aid: 0.1~1 part;

[0012] Component B is an acidic catalyst solution, made from raw materials comprising the following parts by weight:

[0013] Organic acids: 10-20 parts

[0014] Sustained-release formulation: 1-5 parts

[0015] Water: 75-89 parts.

[0016] Preferably, component A is made from raw materials comprising the following parts by weight:

[0017] Modified silica sol: 80 parts

[0018] Furan resin prepolymer: 20 parts

[0019] Penetration aid: 0.5 parts;

[0020] Component B is an acidic catalyst solution, made from raw materials comprising the following parts by weight:

[0021] Organic acids: 15 parts

[0022] Sustained-release formulation: 3 parts

[0023] Water: 80 portions.

[0024] Optionally, the volume ratio of component A to component B is 2 to 5:1.

[0025] Preferably, the volume ratio of component A to component B is 4:1.

[0026] Optionally, the modified silica sol is obtained by composite modification of alkaline silica sol with silane coupling agent KH-560 and citric acid;

[0027] The modified silica sol contains 20-30% SiO2 by mass.

[0028] The modified silica sol has a pH of 4 to 6.

[0029] Preferably, the modified silica sol contains 25% SiO2 by mass.

[0030] The modified silica sol has a pH of 5.

[0031] Optionally, the furan resin prepolymer is a modified copolymer of furfuryl alcohol and urea-formaldehyde prepolymer;

[0032] The viscosity of the furan resin prepolymer at a standard temperature of 25°C is 100~300 mPa·s.

[0033] Preferably, the viscosity of the furan resin prepolymer at a standard temperature of 25°C is 150 mPa·s.

[0034] Optionally, the penetration aid includes fatty alcohol polyoxyethylene ether (JFC).

[0035] The organic acids include oxalic acid or citric acid;

[0036] The sustained-release agent includes triammonium citrate or glycerol.

[0037] On the other hand, this application provides a method for preparing the aforementioned sol-resin slurry, comprising the following steps:

[0038] (1) Mix the modified silica sol with furan resin prepolymer and penetrating agent, stir, and form a uniform and stable light yellow translucent liquid, which is component A;

[0039] (2) Mix the organic acid, the slow-release agent and water, and stir until completely dissolved to obtain a clear acidic catalyst solution, which is component B;

[0040] (3) Mix component A and component B to obtain the sol resin slurry.

[0041] Optionally, in step (1), the preparation steps of the modified silica sol include: under stirring conditions, slowly adding silane coupling agent KH-560 to alkaline silica sol, reacting at 50~60℃ for 2~4h; then cooling to room temperature, adding citric acid, stirring evenly and aging for 24h to obtain the modified silica sol.

[0042] Optionally, the mass fraction of SiO2 in the alkaline silica sol is 25-30%;

[0043] The pH of the alkaline silica sol is 9-10;

[0044] The amount of the silane coupling agent KH-560 added is 3-8% of the weight of the alkaline silica sol;

[0045] The amount of citric acid added is 1-3% of the weight of the alkaline silica sol;

[0046] The stirring speed is 200~400 rpm.

[0047] Preferably, the mass fraction of SiO2 in the alkaline silica sol is 28%;

[0048] The pH of the alkaline silica sol is 9.5;

[0049] The amount of the silane coupling agent KH-560 added is 5% of the weight of the alkaline silica sol;

[0050] The amount of citric acid added is 2% of the weight of the alkaline silica sol;

[0051] The stirring speed is 300 rpm.

[0052] Optionally, in step (1), the stirring speed is 300~500 rpm and the stirring time is 30~60 min.

[0053] Preferably, in step (1), the stirring speed is 500 rpm and the stirring time is 50 min.

[0054] Optionally, in step (2), the stirring speed is 100~300 rpm.

[0055] Preferably, in step (2), the stirring speed is 200 rpm.

[0056] Compared with the prior art, the present invention has at least the following advantages:

[0057] 1. Excellent permeability: The nanoparticle characteristics of the modified silica sol in component A and the introduction of low-viscosity furan resin, combined with the penetrating aid, result in a low initial viscosity of the mixed slurry (<10 mPa·s), which can penetrate into micro-cracks with a width of less than 0.1 mm.

[0058] 2. Controllable gelation and curing time: The organic acids in component B provide H₂. + This triggers the condensation gelation of modified silica sol and the condensation curing of furan resin; the addition of the slow-release agent delays the rapid release of acid, allowing the workable time of the slurry (from mixing to initial setting) to be flexibly adjusted between 30 and 60 minutes (achieved by changing the A:B ratio).

[0059] 3. Synergistically enhanced solidified body properties:

[0060] High strength and toughness: The SiO2 network formed by the modified silica sol provides a rigid framework, and the curing of furan resin fills the network voids and forms an interpenetrating polymer network, which significantly improves compressive strength and flexural strength, and imparts toughness, reducing brittle cracking.

[0061] Strong adhesion: One end of the silane coupling agent KH-560 is bonded to silica sol, while the other end can react with the hydroxyl groups on the surface of furan resin and inorganic substrates (such as rocks and concrete) to form a strong chemical bond, which greatly improves the bonding strength between the solidified body and the substrate.

[0062] Excellent impermeability and durability: The solidified structure is dense and has an extremely low permeability coefficient. Both silica sol and furan resin possess excellent water resistance, acid and alkali resistance, and aging resistance, ensuring long-term impermeability reinforcement effects.

[0063] 4. Environmental friendliness and economy: The main component of this invention is inorganic silica sol, which is environmentally friendly and non-toxic. Furan resin raw materials are widely available. The composite system reduces the amount of high-priced resin used. While achieving or even surpassing the performance of pure organic resin, it is more cost-effective. Detailed Implementation

[0064] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0065] It should be noted that the terms "first," "second," etc., in the specification and claims of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be used interchangeably where appropriate to understand the embodiments of the invention described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion; for example, a product or device comprising a series of units is not necessarily limited to those explicitly listed, but may include other units not explicitly listed or inherent to such products or devices.

[0066] In this invention, the terms "upper," "lower," "left," "right," "front," "rear," "top," "bottom," "inner," "outer," "middle," "vertical," "horizontal," "lateral," and "longitudinal" indicate orientations or positional relationships based on the indicated orientations or positional relationships. These terms are primarily for the purpose of better describing the invention and its embodiments and are not intended to limit the indicated devices, elements, or components to having a specific orientation or to be constructed and operated in a specific orientation.

[0067] Furthermore, some of the aforementioned terms, besides indicating direction or positional relationships, may also have other meanings. For example, the term "above" may, in certain circumstances, indicate a dependency or connection. Those skilled in the art can understand the specific meaning of these terms in this invention based on the specific circumstances.

[0068] Furthermore, the terms "installation," "setup," "equipped with," "connection," "linking," and "socketing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral structure; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium, or an internal connection between two devices, components, or parts. Those skilled in the art can understand the specific meaning of these terms in this invention based on the specific circumstances.

[0069] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to and in conjunction with the embodiments.

[0070] Example 1

[0071] A method for preparing a sol-resin slurry, comprising the following steps:

[0072] (1) Preparation of modified silica sol:

[0073] Under stirring at 200 rpm, 30 g of silane coupling agent KH-560 (purchased from Shaoguan Yang'an Chemical Co., Ltd.) was slowly added to 1000 g of alkaline silica sol (SiO2 mass fraction of 25%, pH of 9, purchased from Hubei Chengfeng Chemical Co., Ltd.), and reacted at 50℃ for 2 h; then cooled to room temperature, 10 g of citric acid (purchased from Jingjing Pharmaceutical Co., Ltd.) was added, stirred evenly and aged for 24 h to obtain modified silica sol with SiO2 mass fraction of 20% and pH of 4.

[0074] (2) Preparation of component A:

[0075] 700g of modified silica sol was mixed with 100g of furan resin prepolymer (the furan resin prepolymer is a modified copolymer of furfuryl alcohol and urea-formaldehyde prepolymer, purchased from Shandong Baofeng New Material Co., Ltd.) with a viscosity (25℃) of 150mPa·s and 1g of penetrating aid (fatty alcohol polyoxyethylene ether (JFC), purchased from Zhejiang Huangma New Material Technology Co., Ltd.) and stirred at 300rpm for 30min to form a uniform and stable light yellow semi-transparent liquid, which is component A.

[0076] (3) Preparation of component B:

[0077] Mix 100g of organic acid (oxalic acid, purchased from Shandong Jinshengrun Chemical Co., Ltd.), 10g of slow-release agent (triammonium citrate, purchased from Jiangsu Kelunduo Food Ingredients Co., Ltd.) with 750g of deionized water, and stir at 100rpm until completely dissolved to obtain a clear acidic catalyst solution, which is component B.

[0078] (4) Slurry preparation:

[0079] In use, the components A and B are mixed at a volume ratio of 2:1 and stirred rapidly until homogeneous to obtain the sol-resin slurry.

[0080] Example 2

[0081] A method for preparing a sol-resin slurry, comprising the following steps:

[0082] (1) Preparation of modified silica sol:

[0083] Under stirring at 300 rpm, 50 g of silane coupling agent KH-560 (purchased from Shaoguan Yang'an Chemical Co., Ltd.) was slowly added to 1000 g of alkaline silica sol (SiO2 mass fraction of 28%, pH of 9.5, purchased from Hubei Chengfeng Chemical Co., Ltd.), and reacted at 55℃ for 3 h; then cooled to room temperature, 20 g of citric acid (purchased from Jingjing Pharmaceutical Co., Ltd.) was added, stirred evenly and aged for 24 h to obtain modified silica sol with SiO2 mass fraction of 25% and pH of 5.

[0084] (2) Preparation of component A:

[0085] 800g of modified silica sol was mixed with 200g of furan resin prepolymer (the furan resin prepolymer is a modified copolymer of furfuryl alcohol and urea-formaldehyde prepolymer, purchased from Shandong Baofeng New Material Co., Ltd.) with a viscosity (25℃) of 150mPa·s and 5g of penetrating aid (fatty alcohol polyoxyethylene ether (JFC), purchased from Zhejiang Huangma New Material Technology Co., Ltd.) and stirred at 500rpm for 50min to form a uniform and stable light yellow semi-transparent liquid, which is component A.

[0086] (3) Preparation of component B:

[0087] Mix 150g of organic acid (oxalic acid, purchased from Shandong Jinshengrun Chemical Co., Ltd.), 30g of slow-release agent (triammonium citrate, purchased from Jiangsu Kelunduo Food Ingredients Co., Ltd.) with 800g of deionized water, and stir at 200rpm until completely dissolved to obtain a clear acidic catalyst solution, which is component B.

[0088] (4) Slurry preparation:

[0089] In use, the components A and B are mixed at a volume ratio of 4:1 and stirred rapidly until homogeneous to obtain the sol-resin slurry.

[0090] Example 3

[0091] A method for preparing a sol-resin slurry, comprising the following steps:

[0092] (1) Preparation of modified silica sol:

[0093] Under stirring at 400 rpm, 80 g of silane coupling agent KH-560 (purchased from Shaoguan Yang'an Chemical Co., Ltd.) was slowly added to 1000 g of alkaline silica sol (SiO2 mass fraction of 30%, pH of 10, purchased from Hubei Chengfeng Chemical Co., Ltd.), and reacted at 60℃ for 4 h; then cooled to room temperature, 30 g of citric acid (purchased from Jingjing Pharmaceutical Co., Ltd.) was added, stirred evenly and aged for 24 h to obtain modified silica sol with SiO2 mass fraction of 30% and pH of 6.

[0094] (2) Preparation of component A:

[0095] 900g of modified silica sol was mixed with 300g of furan resin prepolymer (the furan resin prepolymer is a modified copolymer of furfuryl alcohol and urea-formaldehyde prepolymer, purchased from Shandong Baofeng New Material Co., Ltd.) with a viscosity (25℃) of 150mPa·s and 10g of penetrating aid (fatty alcohol polyoxyethylene ether (JFC), purchased from Zhejiang Huangma New Material Technology Co., Ltd.) and stirred at 400rpm for 60min to form a uniform and stable light yellow semi-transparent liquid, which is component A.

[0096] (3) Preparation of component B:

[0097] Mix 200g of organic acid (oxalic acid, purchased from Shandong Jinshengrun Chemical Co., Ltd.), 50g of slow-release agent (glycerol, purchased from Jinan Jinhao Chemical Co., Ltd.) with 890g of deionized water, and stir at 300rpm until completely dissolved to obtain a clear acidic catalyst solution, which is component B.

[0098] (4) Slurry preparation:

[0099] In use, the components A and B are mixed at a volume ratio of 5:1 and stirred rapidly until homogeneous to obtain the sol-resin slurry.

[0100] Comparative Example 1

[0101] The only difference from Example 2 is that furan resin prepolymer is not added to component A:

[0102] (1) Preparation of modified silica sol:

[0103] Under stirring at 300 rpm, 50 g of silane coupling agent KH-560 (purchased from Shaoguan Yang'an Chemical Co., Ltd.) was slowly added to 1000 g of alkaline silica sol (SiO2 mass fraction of 28%, pH of 9.5, purchased from Hubei Chengfeng Chemical Co., Ltd.), and reacted at 55℃ for 3 h; then cooled to room temperature, 20 g of citric acid (purchased from Jingjing Pharmaceutical Co., Ltd.) was added, stirred evenly and aged for 24 h to obtain modified silica sol with SiO2 mass fraction of 25% and pH of 5.

[0104] (2) Preparation of component A:

[0105] Mix 800g of modified silica sol with 5g of penetration aid (fatty alcohol polyoxyethylene ether (JFC), purchased from Zhejiang Huangma New Material Technology Co., Ltd.), and stir at 500rpm for 50min to obtain component A.

[0106] (3) Preparation of component B:

[0107] Mix 150g of organic acid (oxalic acid, purchased from Shandong Jinshengrun Chemical Co., Ltd.), 30g of slow-release agent (triammonium citrate, purchased from Jiangsu Kelunduo Food Ingredients Co., Ltd.) with 800g of deionized water, and stir at 200rpm until completely dissolved to obtain a clear acidic catalyst solution, which is component B.

[0108] (4) Slurry preparation:

[0109] When using, mix component A and component B at a volume ratio of 4:1 and stir quickly until homogeneous to obtain a slurry.

[0110] Comparative Example 2

[0111] The only difference from Example 2 is that modified silica sol is not added to component A, and component B is a conventional 20% benzenesulfonic acid aqueous solution.

[0112] (1) Preparation of component A:

[0113] 200g of furan resin prepolymer (the furan resin prepolymer is a modified copolymer of furfuryl alcohol and urea-formaldehyde prepolymer, purchased from Shandong Baofeng New Material Co., Ltd.) with a viscosity (25℃) of 150mPa·s was mixed with 5g of penetrating aid (fatty alcohol polyoxyethylene ether (JFC), purchased from Zhejiang Huangma New Material Technology Co., Ltd.) and stirred at 500rpm for 50min to obtain component A.

[0114] (2) Component B uses a 20% benzenesulfonic acid aqueous solution.

[0115] (3) Slurry preparation:

[0116] When using, mix component A and component B at a volume ratio of 4:1 and stir quickly until homogeneous to obtain a slurry.

[0117] Comparative Example 3

[0118] The difference from Example 2 is the use of unmodified alkaline silica sol:

[0119] Preparation of component A:

[0120] 800g of alkaline silica sol (SiO2 mass fraction 28%, pH 9.5, purchased from Hubei Chengfeng Chemical Co., Ltd.) was mixed with 200g of furan resin prepolymer (the furan resin prepolymer is a modified copolymer of furfuryl alcohol and urea-formaldehyde prepolymer, purchased from Shandong Baofeng New Material Co., Ltd.) with a viscosity (25℃) of 150mPa·s and 5g of penetrating aid (fatty alcohol polyoxyethylene ether (JFC), purchased from Zhejiang Huangma New Material Technology Co., Ltd.). The mixture was stirred at 500rpm. Due to the high pH of the system, flocculation occurred quickly after mixing, and a stable and uniform slurry could not be formed, resulting in the failure of the experiment.

[0121] Test Example 1

[0122] To evaluate the performance of the slurry and its solidified form in the embodiments and comparative examples of the present invention, the following tests were conducted:

[0123] Slurry performance test: After mixing components A and B in proportion, immediately test the initial viscosity (rotational viscometer, 25℃) and record the slurry workability time (time from mixing to the slurry losing fluidity) and initial setting time (Vicat method).

[0124] Solidified body performance test: The mixed slurry was injected into the mold and cured for 28 days under standard curing conditions (temperature 20±2℃, relative humidity ≥95%).

[0125] Compressive strength and flexural strength: tested according to GB / T 17671-2021.

[0126] Bond strength: The figure-eight tensile method was used to test the bond tensile strength between the consolidated body and the standard cement mortar specimen.

[0127] Permeability coefficient: The solidified body is made into a cylindrical specimen and tested using a variable head permeameter.

[0128] Acid and alkali corrosion resistance: The solidified specimens were immersed in 5% HCl solution and 5% NaOH solution for 30 days respectively, and their mass change rate and strength retention rate were measured.

[0129] The test results are detailed in Tables 1 and 2.

[0130] Table 1. Results of Slurry Performance Tests

[0131] Example 1 7.8 30 50 Example 2 8.5 45 65 Example 3 9.2 60 85 Comparative Example 1 6.0 20 35 Comparative Example 2 150 (before mixing) 25 40 Comparative Example 3 Unstable, flocculation - -

[0132] As shown in Table 1, the initial viscosity of the slurry in the embodiments of the present invention is all below 10 mPa·s, far lower than that of Comparative Example 2 (pure resin slurry, with a high viscosity before mixing), demonstrating excellent penetration and injection capabilities. By adjusting the ratio, the workable time can be effectively controlled within the range of 30-60 minutes to meet different engineering needs. Comparative Example 3, due to the lack of modification of the silica sol, has poor compatibility with the resin and cannot form a usable slurry. In addition, although the slurry of Comparative Example 1 (pure modified silica sol) has a lower initial viscosity, its solidified body has low strength and high brittleness, failing to meet the reinforcement requirements. The present invention, by introducing a specific proportion of furan resin prepolymer, although slightly increasing the initial viscosity of the slurry, still maintains it at an extremely low level (<10 mPa·s), ensuring excellent permeability. More importantly, the resulting inorganic-organic interpenetrating network structure improves the compressive, flexural, and bonding strength of the solidified body by several times, solving the industry problem of insufficient strength in low-viscosity slurries and achieving an optimal balance between permeability and reinforcement performance.

[0133] Table 2 Results of solidified body performance tests (after 28 days of curing)

[0134] Example 1 38.7 7.6 3.5 <![CDATA[5.1×10 -9 ]]> 93% 97% Example 2 42.5 8.2 3.8 <![CDATA[4.2×10 -9 ]]> 95% 98% Example 3 45.1 8.5 4.0 <![CDATA[3.8×10 -9 ]]> 96% 99% Comparative Example 1 15.3 2.1 1.5 <![CDATA[2.0×10 -8 ]]> 99% 100% Comparative Example 2 35.8 6.5 2.9 <![CDATA[8.5×10 -9 ]]> 85% 90%

[0135] As shown in Table 2, the compressive, flexural, and bond strengths of the embodiments of the present invention (such as Example 2, compressive strength 42.5 MPa, flexural strength 8.2 MPa) are significantly higher than those of Comparative Example 1 (pure silica sol, brittle and low strength) and Comparative Example 2 (pure resin). This demonstrates the synergistic reinforcing effect of the modified silica sol and furan resin. Furthermore, the permeability coefficient of the embodiments of the present invention is as low as 10. -9 The speed per second (cm / s) is superior to Comparative Examples 1 and 2, indicating that the composite solidified body is more dense. Furthermore, the embodiments of the present invention exhibit strength retention rates exceeding 95% in both acidic and alkaline environments, demonstrating excellent corrosion resistance, particularly superior to Comparative Example 2 (where the strength of pure resin decreases significantly in acid). This is attributed to the good chemical stability of the silica sol network and the buffering effect of the composite system against acidic corrosion.

[0136] In summary, the sol-resin slurry provided by this invention organically combines the advantages of modified silica sol and furan resin, achieving a solidified body with high strength, high adhesion, high impermeability, and excellent durability while maintaining excellent injectability. It has broad application prospects in the field of soil and concrete seepage prevention and reinforcement.

[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sol-resin slurry, characterized in that, Includes component A and component B; Component A is made from the following raw materials in parts by weight: Modified silica sol: 70-90 parts Furan resin prepolymer: 10-30 parts Penetration aid: 0.1~1 part; Component B is an acidic catalyst solution, prepared from the following raw materials in parts by weight: Organic acids: 10-20 parts Sustained-release formulation: 1-5 parts Water: 75-89 parts; The volume ratio of component A to component B is 2~5:1; The modified silica sol was obtained by composite modification of alkaline silica sol with silane coupling agent KH-560 and citric acid. The modified silica sol contains 20-30% SiO2 by mass. The pH of the modified silica sol is 4-6; The furan resin prepolymer is a modified copolymer of furfuryl alcohol and urea-formaldehyde prepolymer; The viscosity of the furan resin prepolymer at a standard temperature of 25°C is 100~300 mPa·s; The penetration aid includes fatty alcohol polyoxyethylene ether; The organic acid is oxalic acid or citric acid; The sustained-release agent is triammonium citrate or glycerol.

2. The method for preparing a sol-resin slurry according to claim 1, characterized in that, Includes the following steps: (1) Mix the modified silica sol with furan resin prepolymer and penetrating agent, stir, and form a uniform and stable light yellow translucent liquid, which is component A; (2) Mix the organic acid, the slow-release agent and water, and stir until completely dissolved to obtain a clear acidic catalyst solution, which is component B; (3) Mix component A and component B to obtain the sol resin slurry.

3. The method for preparing a sol-resin slurry according to claim 2, characterized in that, In step (1), the preparation steps of the modified silica sol include: under stirring conditions, slowly adding silane coupling agent KH-560 to alkaline silica sol, reacting at 50~60℃ for 2~4h; then cooling to room temperature, adding citric acid, stirring evenly and aging for 24h to obtain the modified silica sol.

4. The method for preparing a sol-resin slurry according to claim 3, characterized in that, The mass fraction of SiO2 in the alkaline silica sol is 25-30%. The pH of the alkaline silica sol is 9-10; The amount of the silane coupling agent KH-560 added is 3-8% of the weight of the alkaline silica sol; The amount of citric acid added is 1-3% of the weight of the alkaline silica sol; The stirring speed is 200~400 rpm.

5. The method for preparing a sol-resin slurry according to claim 2, characterized in that, In step (1), the stirring speed is 300~500 rpm and the stirring time is 30~60 min.

6. The method for preparing a sol-resin slurry according to claim 2, characterized in that, In step (2), the stirring speed is 100~300 rpm.

Citation Information

Patent Citations

  • Sol resin grout liquid

    CN101955628A

  • Special waterborne curing agent for emery floor

    CN108751908A

  • Two-in-one permeability-modified anticorrosive epoxy coating for concrete surface as well as preparation method and application of two-in-one permeability-modified anticorrosive epoxy coating

    CN109913095A

  • Concrete micro-crack sealing material as well as preparation method and application thereof

    CN110482994A